Geneza „dwóch Testamentów” Pisma Świętego - Królikowski, Janusz (Vox Patrum, 2020)
In the everyday Christian language as well as in theology the two parts of the Holy Bible are referred to as the Old and the New Testament. This terminology has its origins in the Bible, but it was gradually shaped on reflection in the times of the Early Church. It resulted from the process of crystallization of the identity of the Christian community, but also from the fact, that “new” Writings appeared and started to become a part of this identity. Therefore, a need arose for determining their relation to the Jewish Writings and for defining their character which was oriented towards fulfilling the old rules. The article is intended to explain how, in the times of the Early Church, the concept of the “two Testaments” was born.